Invitation to cryptology. - Barr, Thomas H., ....- (New Jersey : Prentice Hall, 2002)
Samenvatting:Designed for either the intelligent freshman (good at math) or for alow-level junior year first course, Cryptology introduces a wide range ofup-to-date cryptological concepts along with the mathematical ideas thatare behind them. The new and old are organized around a historicalframework. A variety of mathematical topics that are germane tocryptology (e.g., modular arithmetic, Boolean functions, complexitytheory, etc.) are developed, but they do not overshadow the main focus ofthe text. Unlike other texts in this field, Cryptology brings studentsdirectly to concepts of classical substitutions and transpositions andissues in modern cryptographic methods.
Keywords: Beveiliging; Cryptografie; Cryptologie